The implementation of artificial intelligence (AI) in education: Patterns, perceptions, and implications for educators and students - Susanto, Darex (Universitas Jambi, Indonesia, 2026)
This study examines the implementation of Artificial Intelligence (AI) in education and its impact on educators and students in Jambi Province, Indonesia. Using a quantitative descriptive design, data were collected through a structured questionnaire administered to 44 respondents, including educators and students. The instrument measured AI usage frequency, digital competence, ethical awareness, and perceived learning effectiveness. Data were analyzed using descriptive statistics, including frequencies, percentages, and mean scores. The findings indicate that AI is frequently used for accessing information and supporting learning tasks; however, respondents demonstrate moderate levels of critical evaluation and ethical awareness in AI utilization. While AI contributes positively to learning efficiency and instructional support, its effectiveness depends on digital literacy competence and responsible usage. The study highlights the need for structured AI literacy training, ethical guidelines, and improved digital infrastructure to ensure sustainable and equitable integration of AI in education.